How to Start a Conversation and Make Friends - Gabor, Don (London Sheldon Press, 1997)
A handbook for the timid and tongue-tied showing how to start a conversation, keep one going, the right questions to ask and how much you should reveal about yourself after saying "hello". In every situation, work, social, meetings or anywhere, the ability to maximize verbal skills is helpful.
Include Illustrations
Keywords: Conversation